2017
DOI: 10.1371/journal.pone.0171237
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive evaluation of facial crestal bone with ultrasonography

Abstract: PurposeFacial crestal bone level and dimension determine function and esthetics of dentition and dental implants. We have previously demonstrated that ultrasound can identify bony and soft tissue structures in the oral cavity. The aim of this study is to evaluate the accuracy of using ultrasound to measure facial crestal bone level and thickness.Materials and methodsA commercially available medical ultrasound scanner, paired with a 14 MHz imaging probe was used to scan dental and periodontal tissues at the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 22 publications
1
63
0
Order By: Relevance
“…A recent proof‐of‐principle study (Chan, Wang, Fowlkes, Giannobile, & Kripfgans, ) showed that ultrasound can image important oral anatomical structures. Later, another study from our group (Chan, Sinjab, et al., ) demonstrated accurate ultrasound readings of alveolar bone height and thickness on human cadaverous specimens. The mean absolute differences in ultrasound measures from direct measures and radiographic measures from CBCT images were within 0.1 mm.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent proof‐of‐principle study (Chan, Wang, Fowlkes, Giannobile, & Kripfgans, ) showed that ultrasound can image important oral anatomical structures. Later, another study from our group (Chan, Sinjab, et al., ) demonstrated accurate ultrasound readings of alveolar bone height and thickness on human cadaverous specimens. The mean absolute differences in ultrasound measures from direct measures and radiographic measures from CBCT images were within 0.1 mm.…”
Section: Introductionmentioning
confidence: 89%
“…The scanning set‐up and procedures were performed by two examiners (HC and OK) based on methods previously described (Chan, Sinjab, et al., ; Chan, Wang, et al., ). A built‐in function of spatial compounding was selected to obtain well‐resolved bone and implant edges (ZS3 Zonare/Mindray, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The ultrasound equipment setups and the scanning procedures were performed by two experienced investigators (HC and OK) (Chan, Sinjab, et al, ; Chan, Wang, et al, ). Three distinct sites, the premolar, molar, and retromolar sites, were selected for imaging (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…In medicine, the use of non‐ionizing ultrasound has been established and advocated for many years (Bhaskar, Chan, MacEachern, & Kripfgans, ; Hoskins & Kenwright, ; Moskalik et al, ; Oelze & Mamou, ). In dentistry, its advantage for providing low‐cost real‐time cross‐sectional images can be quite useful as it relates to providing optimal soft tissue contrast of pertinent anatomical structures and the peri‐implant tissues (Bhaskar et al, ; Chan, Sinjab, et al, ; Chan et al, ). Additionally, ultrasound has been validated for measuring tissue thickness in different locations of the oral cavity (Chan, Sinjab, et al, ; Chan, Wang, Fowlkes, Giannobile, & Kripfgans, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation